2020
DOI: 10.3390/hydrology7020035
|View full text |Cite
|
Sign up to set email alerts
|

Urban Floods: Linking the Overloading of a Storm Water Sewer System to Precipitation Parameters

Abstract: The lack and inefficiency of urban drainage systems, as well as extreme precipitation, can lead to system overloading and, therefore, an urban pluvial flood. The study brings insights into this phenomenon from the perspective of the statistical relationship between precipitation and flooding parameters. The paper investigates the possibility of predicting sewer overloading based on the characteristics of the upcoming rain event using the Storm Water Management Model (SWMM) and statistical methods. Additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The economy can be significantly impacted by severe weather conditions, such as thunderstorms, and human life is at risk [1][2][3][4][5]. While thunderstorms can bring much-needed rain, they can also produce an abundance of precipitation, which can generate floods that harm infrastructure and property [6][7][8][9][10][11][12][13]. Thunderstorms can also produce tornadoes, downbursts, and hail, all of which have the potential to 2 cause significant damage and even fatalities.…”
Section: Introductionmentioning
confidence: 99%
“…The economy can be significantly impacted by severe weather conditions, such as thunderstorms, and human life is at risk [1][2][3][4][5]. While thunderstorms can bring much-needed rain, they can also produce an abundance of precipitation, which can generate floods that harm infrastructure and property [6][7][8][9][10][11][12][13]. Thunderstorms can also produce tornadoes, downbursts, and hail, all of which have the potential to 2 cause significant damage and even fatalities.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have focused on how to reduce the computational burden when analyzing urban drainage systems; either by exploring the link between rainfall properties and overflow phenomena in the sewer systems (Jean et al 2018;McGrath et al 2019), by utilizing machine learning techniques to avoid physics based models for flooding (Löwe et al 2021;Vorobevskii et al 2020) or by introducing model predictive or real time control into the system (Rathnayake and Faisal Anwar 2019;Bachmann-Machnik et al 2021;El Ghazouli et al 2021). Common for all studies is a recognition of the complexity involved in determining the performance of urban drainage systems, and a goal of minimizing the efforts involved in designing, analyzing and operating these systems.…”
Section: Introductionmentioning
confidence: 99%
“…As such, techniques that filter out some of these superfluous jobs could result in much more efficient LTS simulations with a larger percentage of jobs resulting in relevant responses. Jean et al (2018) pointed out that continuous simulations will result in the least erroneous result while Vorobevskii et al (2020) showed how rainfall characteristics could be used to select relevant events in flood modelling. The objective of this study is to determine the rain events to be included on an LTS simulation job list to simulate CSOs, given statistical information from the rainfall time series only.…”
Section: Introductionmentioning
confidence: 99%
“…During extreme heavy rainfall events, the impacts of surface runoff increase rapidly and necessary measures in sewer operation are barely predictable and must be adapted to the situation in each individual case. Each crisis management requires rapid and appropriate action, and most of the time people in charge within the categories listed above have only limited resources at their disposal, which have to be used optimally to deal with the most diverse situations [44][45][46][47]. Consequently, optimal crisis management requires intensive preparation [48][49][50][51], and many municipalities across the world are still seeking more information to make their urban drainage systems more resilient to urban flooding and more adaptable to unpredicted disturbances [52,53].…”
mentioning
confidence: 99%